O palhaço bruto de Timochenco Wehbi - Silva, Elizabete Araujo da (2018)
This work aims at investigating how the plot of the play Palhaços, by Timonchenco Wehbi, can be connected to the basic elements of what Peter Brook has called Rough Theatre: a kind of theatre that, beyond merely proposing the centrality of human actions, brings up at its core the search for a critical positioning of artists and public alike. In order to conduct such an endeavour, we will start by reading and analyzing Palhaços to demonstrate how the reflection of artistic procedures is capable of critically influencing both artists and public, and is intrinsic to Wehbi’s dramaturgical architecture. Thus, it would be possible to compare the latter with the ideas about theatre that Peter Brook puts forth in his work The empty space. Finally, we intend to bring light to the fact that the theatre of provocation and contestation (i.e., the rough) is indeed an aesthetic and thematic project of Wehbi's, which we can access through the conversation between an artist, a clown called Careta, and a man from the public, a shoe seller called Benvindo, both of whom are characters in Palhaços